Partai Islam dalam Pemilu 1955: Pilihan Masyarakat Jawa Barat Berdasarkan Kampanye Pertama di Indonesia - Gian Fajar Gemilang; Toto Suryana; Ganjar Eka Subakti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
A democratic state requires representation as a formal and procedural means of government. The manifestation of the form of democracy in Indonesia that has only been formed a decade is the plan to carry out the first general election that will involve all the people. The election is planned as the number one idea of the state system as well as a step to prepare the draft and regulations of the legislation. Masyumi was the first Islamic party to gain great support from various groups of people. After a conflict based on ideological differences between groups in Masyumi's body, slowly one by one Islamic organizations retreated and formed a political party that stood alone. Nu who had split later founded a political party as a competitor of Masyumi. With a number of times not less, both were included in the top five political parties winning the 1955 election. Campaigning as a tool as well as communication of the political elite became very important in that period with a focus on the media as well as the message delivered. West Java region became an example of the success of the campaign conducted by Masyumi with the most votes among other political parties.